Compiler support for work-stealing parallel runtime systems - Raman, Raghavan (ProQuest Dissertations & Theses, 2009)
Multiple programming models are emerging to address an increased need for dynamic task parallelism in applications for multicore processors and shared-address-space parallel computing. Examples include OpenMP 3.0, Java Concurrency Utilities, Microsoft Task Parallel Library, Intel Threading Building Blocks, Cilk, X10, Chapel, and Fortress. Scheduling algorithms based on work-stealing, as embodied in Cilk's implementation of dynamic spawn-sync parallelism, are gaining in popularity but also have inherent limitations. In this thesis, we focus on the compiler support needed to extend work-stealing for dynamic async-finish task parallelism as in X10 and HabaneroJava (HJ). We also discuss the compiler support needed for work-stealing with both the work-first and help-first policies. Performance results obtained using our compiler and the HJ work-stealing runtime show significant improvement compared to the earlier work-sharing runtime. We then propose and implement two optimizations that can be performed in the compiler to improve the code generated for work-stealing schedulers. Performance results show that the Frame-Store optimizations provide a significant reduction in the code size and the number of frame-store statements executed dynamically, but these reductions do not result in execution time improvements on current multicore systems. We also show that the Objects-As-Frames optimization yields an improvement in performance for small number of threads. Finally, we propose topics for future work which include extending work-stealing for additional language constructs as well as new optimizations.